Innovative Water Purification Using Pineapple By-Product and Rice Husk: A Portable Filtration Approach - Azizul, Nurfatin Nadiha; Mohd Mahat, Maizatul Sofea; Ab Razak, Siti Noraiza; Adnan, Nurul Nadia (Multidisciplinary Applied Research and Innovation, 2025)
The goal of this study is to address the dual challenges of providing clean water and reducing environmental waste by creating a filtration system that is easy to make, affordable and suitable for areas with limited access to clean water. Four types of activated carbon (AC) were prepared using heating method with different combinations of rice husk (RH) and pineapple waste (PW) (Sample A - 100% RH; Sample B - 100% PW; Sample C - 3:7 RH to PW; Sample D – 3:7 PW to RH). These AC were then employed into a portable water filter, separately to purify the river water. The water quality was analyzed based on its Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), ammoniacal nitrogen, Total Suspended Solids (TSS), Total Dissolved Solids (TDS), turbidity, Dissolved Oxygen (DO) and pH level. Sample C shows the best performance among other type of AC where the BOD is 67.76% , COD is 68%, ammoniacal nitrogen is 70.49%, TSS is 67.91%, DO is 54.84%, TDS is 58.19%, and turbidity is 71.03% compared with the real standard